The Effectiveness of Parole Supervision: Use of Propensity Score Matching to Analyze Reincarceration Rates in Kentucky: - Vito, Gennaro Francis (Criminal justice policy review, 2017)
Recent years have seen increasing concerns about the importance of offender reentry and how to best facilitate ex-offenders remaining crimefree. Common responses have been to enhance punitiveness, and to decrease resources and support services for ex-offenders. Results have been consistently high levels of recidivism, and consequently increasingly punitive responses. The present study examines whether a cohort of offenders released to the community in Kentucky either under parole supervision or at the expiration of their sentences are more likely to be reincarcerated within a 5-year period. The participants of each cohort were constructed into two groups using propensity score matching to control for differences between them.